The Effect of Work Motivation and Leadership Style on Teacher Performance at SMA Negeri 2 Pangururan - Sinurat, Riomas; Fachri Setiadi; Nurmalini (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
This study aims to examine and analyze the effect of work motivation and leadership style on the performance of teachers at SMA Negeri 2 Pangururan Samosir. To collect the research data, the researcher distributed questionnaires to 25 teachers at SMA Negeri 2 Pangururan Samosir. The data processing results indicate that there is an effect of work motivation on teacher performance at SMA Negeri 2 Pangururan Samosir, as evidenced by the analysis, which yielded a t-value of 4.931 with a significance level of 0.000. Data processing also proves that there is an effect of leadership style on teacher performance, with the analysis showing a t-value of 2.157 and a significance level of 0.042. Simultaneous testing also proves that work motivation and leadership style have a positive and significant effect on teacher performance. This can be seen from the F-test result of 36.238 and a significance level of 0.000, meaning that the independent variables, namely work motivation and leadership style, simultaneously influence the dependent variable, which is teacher performance at SMA Negeri 2 Pangururan.